Synchiropus sechellensis Regan, 1908 (Teleostei: Callionymidae), a new Lessepsian migrant in the Mediterranean Sea - GÖKOĞLU, M.; ÖZVAROL, Y.; FRICKE, R. (Mediterranean Marine Science, 2014)
A new Lessepsian migrant, Synchiropus sechellensis Regan, 1908 (Teleostei: Callionymidae), was recorded for the first time by a single male specimen, during bottom trawl operation in the Mediterranean Sea.